Changes in the global burden of depression from 1990 to 2017: Findings from the Global Burden of Disease study - Liu, Qingqing; He, Hairong; Yang, Jin; Feng, Xiaojie; Zhao, Fanfan; Lyu, Jun (Journal of psychiatric research, 2020)
Depression is the most common mental illness worldwide. It has become an important public health problem. This study aimed to determine the global burden of depression and how it has changed between 1990 and 2017. We used information on depression obtained by the Global Burden of Disease (GBD) study from 1990 to 2017. The age-standardized incidence rate (ASR) and estimated annual percentage change (EAPC) were used to assess the global burden of depression. The number of incident cases of depression worldwide increased from 172 million in 1990 to 25,8 million in 2017, representing an increase of 49.86%. The ASR of depression varied widely between the 195 analyzed countries and regions in 2017, being highest in Lesotho (6.59 per 1000) and lowest in Myanmar (1.28 per 1000). The ASR increased the most between 1990 and 2017 in Belgium (EAPC = 0.88, 95% confidence interval [CI] = 0.78 to 0.97), and decreased the most in Cuba (EAPC = −1.26, 95% CI = −1.36 to −1.14). The ASR increased in regions with a high sociodemographic index, such as high-income North America (EAPC = 0.41, 95% CI = 0.31 to 0.51), and decreased significantly in South Asia (EAPC = −0.63, 95% CI = −0.85 to −0.41). The proportions of the population with major depressive disorder and dysthymia were essentially stable both globally and in various countries, with a much larger proportion having major depressive disorder. Depression remains a major public health issue, and governments should support the research necessary to develop better prevention and treatment interventions.